2010
DOI: 10.1523/jneurosci.0252-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Striatal Overexpression of ΔFosB Reproduces Chronic Levodopa-Induced Involuntary Movements

Abstract: Long-term dopamine replacement therapy in Parkinson's disease leads to the development of disabling involuntary movements named dyskinesias that are related to adaptive changes in striatal signaling pathways. The chronic transcription factor ⌬FosB, which is overexpressed in striatal neurons after chronic dopaminergic drug exposure, is suspected to mediate these adaptive changes. Here, we sought to demonstrate the ability of ⌬FosB to lead directly to the abnormal motor responses associated with chronic dopamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
66
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 46 publications
10
66
0
Order By: Relevance
“…Moreover, dyskinetic, chronically L-DOPA-treated mice exhibited higher DFosB levels than nondyskinetic mice chronically treated with L-DOPA (Pavon et al, 2006). Furthermore, and this is perhaps the most convincing evidence in favor of a direct etiological role of DFosB in LID, striatal overexpression of DFosB induced by viral vector led to the development of a dyskinetic phenotype similar to LI-AIMs, in the absence of L-DOPA administration, in the 6-OHDA-lesioned rat (Cao et al, 2010). In addition, in a study performed in the MPTP-lesioned macaque, a linear relationship was demonstrated between striatal DFosB levels and dyskinesia severity (Berton et al, 2009).…”
Section: A Transcription Factorsmentioning
confidence: 87%
“…Moreover, dyskinetic, chronically L-DOPA-treated mice exhibited higher DFosB levels than nondyskinetic mice chronically treated with L-DOPA (Pavon et al, 2006). Furthermore, and this is perhaps the most convincing evidence in favor of a direct etiological role of DFosB in LID, striatal overexpression of DFosB induced by viral vector led to the development of a dyskinetic phenotype similar to LI-AIMs, in the absence of L-DOPA administration, in the 6-OHDA-lesioned rat (Cao et al, 2010). In addition, in a study performed in the MPTP-lesioned macaque, a linear relationship was demonstrated between striatal DFosB levels and dyskinesia severity (Berton et al, 2009).…”
Section: A Transcription Factorsmentioning
confidence: 87%
“…However, the cited studies did not distinguish between occurrence and absence of dyskinesia and the observed average increase may be predominantly due to dyskinetic animals, as seen in our results. Furthermore, there is convincing evidence that above a critical threshold DFosB is causally linked to LID, as its striatal overexpression in rats induced by viral vectors provoked dyskinesia even without L-DOPA administration (Cao et al, 2010) and as molecular interventions reducing DFosB activity attenuated the severity of already established LID in different animal models of PD (Berton et al, 2009;Engeln et al, 2014).…”
Section: Plasticity Of Th+ Neurons In Lid and Following L-dopa Treatmentmentioning
confidence: 99%
“…In fact, research is in progress in numerous laboratories to investigate the antidyskinetic potential of drugs directed to various molecular targets linked to the nigrostriatal system, including the glutamatergic, GABAergic, adenosine, cannabinoid, noradrenergic, and other systems (Carta et al, 2008a;Fox et al, 2008;Jenner, 2008a,b;Cao et al, 2010;Lebel et al, 2010;Morin et al, 2010). Work is also being done to investigate the antidyskinetic potential of nicotine and nAChR-directed ligands in view of the extensive nicotinic cholinergic innervation in the nigrostriatal system (Quik et al, 2009).…”
Section: Quik and Wonnacottmentioning
confidence: 99%